Regeneration of the skin of oncology patients after radiation therapy using upcycled fish collagen - Igielska-Kalwat, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Introduction: Oncological therapy is a very complex process. An accurate diagnosis is the first and most important stage of therapy for the patient as it allows the medical staff to determine what treatment is necessary and how to plan it. Cancer treatment is now widely recognized as holistic, in which the body is viewed as one interconnected system. Cancer therapy should not focus on just one area of care, but should also include treatment support such as proper nutrition, pain management, psychological care, rehabilitation and nursing. Cancer therapy, despite its effectiveness, has a number of negative effects felt mainly in the area of the skin subjected to irradiation. Side effects significantly affect the patient’s quality of life through pain, discomfort and a negative impact on the aesthetic value of the skin. Aim: The aim of the article was to confirm the level of hydration, limit excessive water loss and regulate the pH value of the skin of patients after cancer treatment who were administered fish collagen. Material and methods: The cosmetic preparation collagen laminate obtained by ultrafiltration was tested on patients who underwent therapy at the University Hospital in Zielona Gora and who underwent radiotherapy. Patients are currently no longer undergoing treatment. The research group of 50 women suffered from breast cancer (n = 50). Before the experiment, the patients’ skin was examined to diagnose its condition (zero condition). The study was conducted with the consent of the Bioethics Committee in Poznan (consent number 692/23). Each participant received a commercial cosmetic preparation. People who underwent radiotherapy applied the cosmetic to the area exposed to radiation, i.e., their breasts. Patients used the preparation twice a day, in the morning and in the evening. The preparation was used to eliminate skin reactions to oncological treatment. The study lasted 6 months. Then, digital measurements were performed monthly using a Courage + Khazaka Electronic GmbH device to measure hydration, transepidermal water loss (TEWL) and pH value. Results: Already after the first use, the device’s skin hydration level increases by 5 a.u. In the next month it increased by 15 a.u. and in the fourth month it increased by 30 IU. Staff skin hydration levels increased linearly over time. After 5 parameters enabling 55 [a.u.] and after 6 a.m., another one until 6 a.m. [a.u.]. The average TEWL value measured in patients after radiotherapy was 40 g/m2/h. With the duration of the study/During the study, the TEWL parameter gradually improved, oscillating after 6 months of study at an average level of 6 g/m2/h. X-ray therapy also has an adverse effect on the condition of the skin, increasing the normal slightly acidic reaction on the skin surface. Based on the research, it was found that the longer the time since the end of the therapy, the less alkaline the pH became. Conclusions: It was confirmed that the product tested for an oncological patient has an appropriate level of skin hydration, supports the reconstruction of the skin and its energy barrier by reducing transepidermal water loss and restoring appropriate pH values.